Konseling Islam dengan Do’a dan Teknik Desensitisasi Sistematik untuk Mengurangi Phobia Kucing (Ailurophobia) - Risatur Rofi'ah (Institut Pesantren Sunan Drajat Lamongan, Indonesia, 2022)
Phobia is quite serious problems that can be suffered by a person. Phobia will be dangerous if not treated immediately, which will cause muscle tension, panic, headaches, palpitations, hysterics, excessive fear etc. Phobia is a natural thing that some people have, this is caused by a fear or trauma of something that happened in the past. Phobia can be said to be unnatural if someone is afraid of certain objects that are considered by most people not scary, for example phobia of cats. This will be very dangerous if not addressed immediately, because these feelings and fears are very disturbing psychologically and very influential in everyday life. One of the efforts made to overcome the phobia of cats is through Islamic counseling with prayer and systematic desensitization techniques. Through prayer and surrender, the counselee is expected to be able to surrender to the Creator. By always remembering Allah SWT, surely all kinds of anxiety and fear will soon disappear. Through the systematic desensitization hoped that the client can overcome phobia by replacing excessive fear and anxiety with a calmer feeling. The counseling process is carried out with Treatment which is done by adding prayer to the systematic desensitization in the relaxation section to reduce phobia. This study uses a qualitative research method with the type of case study research. Data collection is done through interviews, observation, and documentation. While the data analysis technique used is comparative descriptive by comparing theoretical and field data and the results before and after counseling is done. The results of this study indicate that there is a change in the counselee's self, namely in the form of decreased Phobia symptoms which are characterized by self-control and changing behavior for the better.